Transformations between tetrahedrally and octahedrally coordinated crystals: the wurtzite -> rocksalt and blende -> rocksalt mechanisms - Wilson, M; Madden, P (2002)
The mechanism of the pressure-driven phase transformation from the wurtzite (B4) to rocksalt (B1) crystal structures is studied in a 'constant-stress' molecular dynamics simulation of a model ionic system. The mechanism differs significantly from that exhibited by the same system in transforming from the zinc blende structure (B3) to rocksalt, despite the fact that the B3 and B4 phases differ only in their stacking sequences. This is traced to the difference between the crystal structures at the next-nearest-neighbour level and discussed in terms of the preponderance of boat and chair six-membered rings within the two structures. The relationship between the observed mechanism and those which have been proposed on the basis of crystallographic studies is explored. In particular the way in which the stability of potential intermediate phases is influenced by the interatomic interactions is discussed.